2013
DOI: 10.1002/ptr.4975
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Puerarin on 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine induced Parkinson's Disease Model in Mice

Abstract: Puerarin, an active component of Pueraria montana var. lobata (Willd.) Sanjappa & Pradeep is well-known for its anti-oxidative and neuroprotective activities. Although anti-Parkinson's disease activity of puerarin was reported in both of in vivo and in vitro model, detailed mechanisms are not clarified. In this study, we addressed that puerarin attenuated 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced behavioral deficits, dopaminergic neuronal degeneration and dopamine depletion. Puerarin administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…5961 . However, not many studies on the antidepressant-like effect of puerarin and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…5961 . However, not many studies on the antidepressant-like effect of puerarin and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, this medicinal herb is used as ethnomedicine for treating various diseases, including neuronal disorders. The reported neuroprotective effects of puerarin (Dong et al, 2015;Li et al, 2013;Zhu et al, 2014) have provided the support for its traditional use as a treatment for neuronal disorders, and reasonably prompted us to investigate the neurotrophic abilities of this ethnomedicine to the development of CNS neurons. It is worth mentioning that the development of a neuron involves a stereotypic progression of events, that is, the initiation of process outgrowth, axonal differentiation, dendritic arborization and the formation of synaptic connections.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence of the neuroprotective effects of puerarin has been provided by a number of in vitro and animal model experiments. Zhu et al (2012Zhu et al ( , 2014 reported that puerarin inhibited MPP þ induced human neuroblastoma cell death by activating the PI3K/Akt pathway, and attenuated MPTP-induced dopaminergic neuronal degeneration by modulating GDNF expression, the PI3K/Akt pathway and glutathione activation in a mouse model of PD. Puerarin attenuates neuronal degeneration by protecting against 6-OHDA-mediated oxidative stress injury in substantia nigra .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that GDNF and brain-derived neurotrophic factor expression levels are upregulated and that cellular apoptosis is attenuated by acupuncture in the hippocampi of rats experiencing hypoxia-ischemia (23). Furthermore, GDNF has a neurotrophic effect on diabetes-induced neuronal apoptosis in the hippocampus (24) and enhances the migration of colon cancer cells (25) via the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%